Yield and quality of guinea grass seed cv. Mombaza at different pre-cut dates - Joaquín Torres, Bertín Maurilio; Gómez-Vázquez, Armando; Ramos Juárez, Jesús Alberto; Aranda Ibañez, Emilio Manuel; Pérez Amaro, José Alberto; Joaquín Cancino, Santiago (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of the present study was to evaluate the effect of the precut in the yield and quality of guinea grass seed (Megathyrsus maximus) cv. Mombasa. The study was carried out in the experimental field of the University of the Papaloapan Campus Loma Bonita, Oaxaca. Eight treatments were evaluated, which consisted in precuts every 10 days from the court of uniformity, which took place on July 1. The treatments were tested under a design of a randomized complete block with three replications per treatment. We evaluated the total seed yield, pure seed yield, yield of pure germinable seed, germination percentage of harvested seed, plant height, total number of panicles per m2, ripe panicle number per m2, panicle length, number of seeds harvested by panicle, seed weight per panicle, percentage of purity and weight of a thousand seeds. There were significant differences (p< 0.05) between treatments for pure seed yield and yield of pure germinable seed, where the highest values (205.2 and 103.1 kg ha-1, respectively) were obtained with the precut the date July 20, there were also significant difference to the number of seeds harvested by panicle and weight of seeds per panicle. It is therefore concluded that the July 20 is the best date for precut to increase seed yield of Megathyrsus maximus cv. Mombaza.